The effect of coffee on metabolic response and exercise in various environmental conditions: a scoping review - Wahab, Nur Farainaa
Introduction: Coffee consists of caffeine which occurs naturally, and has been known to increase metabolic rate. Caffeine is one of the most common ergogenic supplements in sports whose properties believed able to enhance exercise performance better than consuming coffee. The aims to elucidate findings on the effects of coffee, caffeine in combination with additional substances, on metabolic response and exercise performance in various environmental conditions. Methods: Literature was searched based on PRISMA scoping review (PRISMA-ScR) using EBSCOhost, ScienceDirect, PubMed, and Scopus databases of English publications from 2015 to 2021 was conducted. From 240 studies screened, only 20 publications were included. Results: There were five studies investigated coffee, nine studies used caffeine and decaffeinated supplements. Six reported combined effects of coffee with an additional supplement on exercise (soy and extra virgin coconut oil, high carbohydrate (CHO) meal, low calorie CHO (0.4%solution, 2g total CHO), citrus aurantium, dextrose, green coffee-bean extract, 6%CHO solution). 13 studies investigated effect of coffee on exercise performance (endurance, strength and power, time-to-exhaustion). Two studies showed coffee enhanced epinephrine and norepinephrine but not insulin, glucose and triglycerides. Five studies investigated changes in metabolic which showed significant difference (p<0.05) in energy expenditure and rate of perceived exertion, but no differences on the rate of fat and CHO oxidations as well as maximal oxygen uptake (VO2max). Acute ingestion of 3 to 6 mg/kg.body weight caffeine improved endurance performance in two studies, three studies improvements in strength and power (p<0.05). Improvement in time performance was found in three studies, two studies found no improvement in exercise performance of free-throw and sprinting. Conclusion: Coffee or supplements added with caffeine improved exercise or sport performance and metabolic. Caffeine ingestion in dosages between 3 to 6 mg/kg.bw showed significant changes in exercise performance, blood, and metabolic within 60 minutes of ingestion prior to intervention.